Potensi Pengembangan Agroforestri Berbasis Kopi di Hulu DAS Citarum (Potential for Development of Coffee-Based Agroforestry in Upper Citarum Watershed) - Elfira Rosa Juningsih; Ary Widiyanto (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2024)
Coffee cultivation has enormous potential in the southern part of Bandung Regency, which includes the upstream area of ​​the Citarum River Basin (DAS). This study aims to determine the potential for coffee development through agroforestry patterns with pine trees and mixed forests such as rasamala (Altingia excelsa) and puspa (Schima wallichii). This study uses the Institutional Analysis and Development (IAD) method. Data collection was carried out using observation and interview methods. Respondents were the Forest Village Community Institution (LMDH), and key informants included LMDH Management, Perum Perhutani KPH South Bandung staff, extension workers, and coffee traders. Data were analyzed descriptively. The study results showed that farmer institutions had not been properly formed, market access was open but still limited, and government support needed to be increased in mentoring farmer groups. Other results showed that coffee development with an agroforestry pattern was better for the environment than other land uses such as monoculture farming. Although it contributes to farmers' income, coffee cultivation has not been able to become the main source of income for the majority of farmers. Mentoring, counseling, business capital and marketing assistance are needed to ensure that there is no conversion of forest land to other uses and to increase the added value of community coffee products.